Nanoribbons with Nonalternant Topology from Fusion of Polyazulene: Carbon Allotropes beyond Graphene - Fan, Qitang; Martin-Jimenez, Daniel; Ebeling, Daniel; Krug, Claudio K.; Brechmann, Lea; Kohlmeyer, Corinna; Hilt, Gerhard; Hieringer, Wolfgang; Schirmeisen, André; Gottfried, J. Michael (Journal of the American Chemical Society, 2019)
Various two-dimensional (2D) carbon allotropes with nonalternant topologies, such as pentaheptites and phagraphene, have been proposed. Predictions indicate that these metastable carbon polymorphs, which contain odd-numbered rings, possess unusual (opto)electronic properties. However, none of these materials has been achieved experimentally due to synthetic challenges. In this work, by using on-surface synthesis, nanoribbons of the nonalternant graphene allotropes, phagraphene and tetra-penta-hepta(TPH)-graphene, have been obtained by dehydrogenative C-C coupling of 2,6-polyazulene chains. These chains were formed in a preceding reaction step via on-surface Ullmann coupling of 2,6-dibromoazulene. Low-temperature scanning probe microscopies with CO-functionalized tips and density functional theory calculations have been used to elucidate their structural properties. The proposed synthesis of nonalternant carbon nanoribbons from the fusion of synthetic line-defects may pave the way for large-area preparation of novel 2D carbon allotropes. ©
CRIS-Team Scopus Importer:2019-11-08